Health inequalities in infectious diseases: a systematic overview of reviews - Ben Barr; Oyinlola Oyebode; Seun Stephen Anjorin; Noel McCarthy; Iman Ghosh; Abimbola Ayorinde; Iram Zahair; Ifra Ali; Olajumoke Olarewaju; Megha Singh; Edward Meehan; Suzanne Rotheram (BMJ Open)
Objectives The aim of this systematic overview of reviews was to synthesise available evidence on inequalities in infectious disease based on three dimensions of inequalities; inclusion health groups, protected characteristics and socioeconomic inequalities.Methods We searched MEDLINE, Embase, Web of Science and OpenGrey databases in November 2021. We included reviews published from the year 2000 which examined inequalities in the incidence, prevalence or consequences of infectious diseases based on the dimensions of interest. Our search focused on tuberculosis, HIV, sexually transmitted infections, hepatitis C, vaccination and antimicrobial resistance. However, we also included eligible reviews of any other infectious diseases. We appraised the quality of reviews using the Assessment of Multiple Systematic Reviews V.2 (AMSTAR2) checklist. We conducted a narrative data synthesis.Results We included 108 reviews in our synthesis covering all the dimensions of inequalities for most of the infectious disease topics of interest, however the quality and volume of review evidence and consistency of their findings varied. The existing literature reviews provide strong evidence that people in inclusion health groups and lower socioeconomic status are consistently at higher risk of infectious diseases, antimicrobial resistance and incomplete/delayed vaccination. In the protected characteristics dimension, ethnicity, and sexual orientation are important factors contributing to inequalities across the various infectious disease topics included in this overview of reviews.Conclusion We identified many reviews that provide evidence of various types of health inequalities in different infectious diseases, vaccination, and antimicrobial resistance. We also highlight areas where reviews may be lacking. The commonalities in the associations and their directions suggest it might be worth targeting interventions for some high risk-groups that may have benefits across multiple infectious disease outcomes rather than operating purely in infectious disease siloes.